Rancang Bangun Bilah Taperless Jenis Horizontal Axis Wind Turbin Untuk PLTB 500 Watt Dengan Airfoil NACA 6412 Menggunakan Software Qblade - Usman, La Ode; Balaka, Ridway; Imran, Al Ichlas (Teknik Mesin Universitas Halu Oleo, 2021)
Energy demand in Indonesia generally continues to increase due to population growth, one of the most widely used energies is wind energy. The research objectives are to determine the geometry of the blades, design and manufacture the blades suitable for use in moderate winds and to determine the power generated. The research started from determining the geometry of the blades for medium speed wind, then making the blades and then testing the blades. The geometry of the blades formed is tapertlles blades of the horizontal axis wind turbine type NACA 6412 airfaoil using Qblade software. The blade is designed with a blade radius of 0.774 m, the chord is 0.0999 m using mahogany wood material. The manufacturing method used is the manual method with the help of machine tools. The blades are tested for equilibrium, then mounted on the tower, 10 meters high to take the data. The test results show that the blades that have been made work well and produce an average power per second of 58.29 Watt, 90.82 Watt, and 102.00 Watt, for three days of testing.Keywords: Tuperless blades, airfoil naca 6412, qblade, horizontal axis wind turbines, mahogany wood.